A case report of laparoscopic orchopsis for transverse testicular ectopia via the Hesselbach route - Zhuofan, Xu; Xudong, Zhao; Boxiang, Yuan (Frontiers in Pediatrics, 2025)
BackgroundTesticular transverse ectopia (TTE) is a rare congenital abnormality in which both testicles descend into the same hemiscrotum via a solitary inguinal canal. This condition is frequently linked with inguinal hernias and various urogenital irregularities, and it may manifest as an unoccupied opposite scrotum or as a discernible lump in the groin or scrotal area.Patient presentationA 9-month-old boy was diagnosed with a right inguinal hernia, which presented as a 3 cm × 3 cm palpable mass without pain upon examination. During surgery, both testicles were discovered to be undescended, fused by their ligaments, and had independent vas deferens, vascular supplies, and epididymides. The poorly developed testicles were fixed in the scrotum via Hei's triangle. Postoperative follow-up revealed normal testicular positioning, with no retraction, atrophy, or hernia recurrence.ConclusionsOrchiopexy via Hei's triangle is a new surgical option for patients with Type I TTE who have insufficient length spermatic cord blood vessels.